Ethnobotany of Medicinal Plants in Gekbrong Village, Cianjur, West Java - Novia Nurul Khairunnisa; Maryanti Setyaningsih; Ranti An Nisaa; Devi Anugrah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Medicinal plants are an important component of local health practices and biodiversity-based knowledge systems. This study aims to identify medicinal plant species used by the people of Gekbrong Village, Cianjur, West Java, and to describe their plant parts, sources, preparation methods, and perceived benefits. A descriptive quantitative and qualitative approach was applied from January to March 2022 through field exploration, documentation, and interviews with community respondents selected purposively. 30 respondents were selected using purposive sampling by considering the interview results, which showed that they used medicinal plants in their daily lives. The study identified 42 medicinal plant species from 30 families, with Lamiaceae as the most represented family. Leaves were the most frequently used plant part, while boiling was the dominant preparation method. Most plants were obtained from home gardens, indicating the importance of household-level conservation of medicinal plant knowledge. These findings support the need to document local ethnobotanical knowledge and develop educational or conservation materials for younger generations.